Industry 4.0-from Smart Factory to Cognitive Cyberphysical Production System and Cloud Manufacturing - Mladineo, Marko (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on recent developments in new industrial platforms, with Industry 4.0 on its way to becoming Industry 5.0. The book covers smart decision support systems for green and sustainable machining, microscale machining, cyber-physical production networks, and the optimization of assembly lines. The modern multiobjective algorithms and multicriteria decision-making methods are applied to various real-world industrial problems. The emerging problem of cybersecurity in advanced technologies is addressed as well.